The role of digital technologies in the public administration sphere. - Popova, Liubov; Seniv, Bogdan; Korol, Volodymyr; Galushko, Oleksandr; Biriukov, Iegor (Cuestiones Políticas., 2023)
The methodological basis of the research is the institutional approach, which provides for ensuring the eﬀectiveness of the interaction between the components of the institutional system and the mechanisms of its implementation and control over the use of digital technologies and makes it possible to create an eﬀective network of relationships between all levels of the system horizontally and vertically, as well as to increase the efciency of the entire system public administration and the quality of public services. The advantages of the implementation of digital technologies in public administration are highlighted, which makes it possible to: increase the efciency of public administration, reduce administrative costs, improve the quality of public services and ensure their availability, and reduce the level of corruption. The results of the implementation of digitalization of public services in the EU countries were analyzed in accordance with the program for the implementation of digitalmeasures within the framework of the Recovery and Sustainability Fund. The necessary directions for the activation of the implementation of digital technologies in the public administration system are substantiated.
Keywords: digital technologies; digital public services; public administration